(untitled) (Gragoatá, 2018)
Seeing was written by José Saramago in 2004, and starts from the assumption that the population can start a silent backlash by casting blank votes in local elections, thus disrupting the normality of the democratic system. Between culpability and action, free choice and the decline of human rights, this book questions the authenticity of democracy as it stands in the present Western societies. Confronted with the dangers of a biopolitical manipulation, casting blank votes hints the potency of a state of exception, in which the population can exercise power based on conscience. This essay looks into the confronting positions of the ruling power and of the population that is governed by that very power. —————————————————————————————- O LIMIAR DA DEMOCRACIA EM ENSAIO SOBRE A LUCIDEZ, DE JOSÉ SARAMAGO Ensaio sobre a Lucidez> é uma obra de José Saramago publicada em 2004 que aponta como hipótese uma revolta silenciosa por parte da população ao votar em branco nas eleições autárquicas e assim desestruturar a normalidade do sistema democrático. Entre a culpabilidade e a ação, entre a livre escolha e a sonegação dos direitos humanos, esta obra questiona a autenticidade da democracia tal como é exercida atualmente nas sociedades ocidentais. Face aos perigos de uma manipulação biopolítica, votar em branco indicia a potência de um estado de exceção, em que a população possa exercer um poder baseado na consciência. Este ensaio indaga os meandros do confronto de posições entre as forças do poder instituído e a população que é governada por essas forças. — Artigo em inglês. — DOI: http://dx.doi.org/10.22409/gragoata.2018n45a1099.